Copyright Protection of Songwriters in Indonesia - Imelda Martinelli; Fricila Anggitha Sugiawan; Kevin Anandita Rukmana (CV. Rayyan Dwi Bharata, 2023)
Intellectual property is an object resulting from human intellectual activity, which is expressed in the form of copyrighted works or inventions. The issue of intellectual property for Indonesian songwriters has never been a good thing. This study uses a prescriptive legal method and examines law as a norm with misconceptions about legal protection. Secondary data becomes the main data. The specifications used are descriptive specifications. Copyright owners enjoy legal protection from the moment their work is transformed into a concrete form that complies with the Declarative Principles. Even if a work is protected because it can be clearly identified, the copyright owner must register the work in the Copyright Register for formal verification. There are two ways to resolve copyright disputes: litigation and non-litigation. Settlements outside the court include advice, mediation, negotiation, mediation, and arbitration. On the other hand, there are two pathways in litigation, one of which is the civil route. Violations can be subject to sanctions in the form of imprisonment and fines as stipulated in the copyright law.